Determinants of inflation and price level differentials across the euro area countries - Malin Andersson; Klaus Masuch; Marc Schiffbauer (European Central Bank (ECB), 2009)
This paper analyses the determinants of inflation differentials and price levels across the euro area countries. Dynamic panel estimations for the period 1999-2006 show that inflation differentials are primarily determined by cyclical positions and inflation persistence. The persistence in inflation differentials appears to be partly explained by administered prices and to some extent by product market regulations. In a cointegrating framework we find that the price level of each euro area country is governed by the levels of GDP per capita.
Keywords: E32; E52; E43; F2; 330; convergence; inflation differentials; Inflation persistence; price level; Inflation; Konjunktur; Zinsstruktur; Wirtschaftliche Konvergenz; Eurozone; EU-Staaten